ANALISIS PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN, USIA DAN PERTUMBUHAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Michael Dimitri; Sumani Sumani (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2014)
The Company Capital Structure plays an important role in the financing of a company. Planning a good capital structure is an important tool to understand since with the right decision of the appropriate capital structure, the company can reduce the cost of capital (cost of capital), which means to increase the value of the company. The author conducted a research to analyze the influence of several variables, namely liquidity, profitability, size, age and growth on capital structure. The data analyzed are generated from the companies in the list LQ 45 in IDX. The author uses multiple linear regression to analyze the data. The results shows that the variables of liquidity, profitability, size, age and growth of the company negatively affect the capital structure. Of these variables only variable of growth that has a significant at alpha level of 10%.